Adequacy of the Endometrial Samples Obtained by the Uterine Explora Device and Conventional Dilatation and Curettage: A Comparative Study - Arafah, Maria Abdulrahim; Cherkess Al-Rikabi, Ammar; Aljasser, Rakia; Adi, Yaser (International Journal of Reproductive Medicine, 2014)
Aims. Our aim is to compare the adequacy and diagnostic yield of samples obtained by the endometrial Explora Sampler I-MX120 with endometrial specimens obtained by conventional dilatation and curettage (D&C). Methods. A total of 1270 endometrial samples were received in the histopathology laboratories at the King Khalid University Hospital, Riyadh, Saudi Arabia, between 2007 and 2010. In the outpatient clinic, the Uterine Explora Model I was used to obtain 996 samples. The remaining 274 samples were obtained by conventional D&C. Sample adequacy and the clustering of inadequate specimens according to age groups by the two different techniques were compared and statistically analyzed. Results. Out of 1270 endometrial samples, 253 (19.9%) were inadequate. The Uterine Explora was used in 88.5% of these inadequate samples (253 samples), and the remaining 11.5% were obtained by D&C. The insufficient tissue incidence was higher with the Explora (17.6%) than with the D&C (2.2%) and the difference was statistically significant (P<0.0001). The ages of the patients, as well as the clinical indications for the procedures, were recorded. Conclusion. This retrospective study demonstrated better specimen adequacy when D&C was used compared to the higher rate of sample insufficiency obtained with the Explora.